Automatic room power control / Ahmad Zakwan Rodzuan, Muhamad Nasharudin Ab Rahim and Emir Asyraf Ahmad Saifuddin - Rodzuan, Ahmad Zakwan; Ab Rahim, Muhamad Nasharudin; Ahmad Saifuddin, Emir Asyraf (2013)
"Automatic Power Control Room" function to avoid wasting electricity and causing thinning ozone layer. The system will detect the movement of a person if in use in the room. But our tools are suitable for the small number of people in and out a little bit. If one has access to the room or area to detect it through the movement of a set of electric power will live immediately. When one is out of the room immediately electric power will be set off. Tools that can be set are as lights, fans, air conditioning and so does not interfere with work. Thus, using this system, electrical power dissipation can be reduced.